2010
DOI: 10.1073/pnas.1006749107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the human circadian system, exercise, and their interaction on cardiovascular function

Abstract: The risk of adverse cardiovascular events peaks in the morning (≈9:00 AM) with a secondary peak in the evening (≈8:00 PM) and a trough at night. This pattern is generally believed to be caused by the day/night distribution of behavioral triggers, but it is unknown whether the endogenous circadian system contributes to these daily fluctuations. Thus, we tested the hypotheses that the circadian system modulates autonomic, hemodynamic, and hemostatic risk markers at rest, and that behavioral stressors have differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
249
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(262 citation statements)
references
References 49 publications
5
249
0
8
Order By: Relevance
“…However, several studies have confirmed the occurrence of more events in the morning than in the evening (Atkinson et al, 2010;Mulcahy et al, 1988;Scheer et al, 2010). Two peaks of onset of cardiac events were found: a high frequency of cardiac events in the hours after rising in the morning and in the evening hours (Atkinson et al, 2010;Hjalmarson et al, 1989;Mulcahy et al, 1988;Muller, 1987).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, several studies have confirmed the occurrence of more events in the morning than in the evening (Atkinson et al, 2010;Mulcahy et al, 1988;Scheer et al, 2010). Two peaks of onset of cardiac events were found: a high frequency of cardiac events in the hours after rising in the morning and in the evening hours (Atkinson et al, 2010;Hjalmarson et al, 1989;Mulcahy et al, 1988;Muller, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…Key words were as follows: circadian variation, sleep, ischemic episodes, cardiac events, cardiac disease, autonomic nervous system activation, physical stress (abrupt upright posture), mental stress, endothelial response of the coronary blood vessels, morning surge of blood pressure, and blood components (Carnethon et al, 2002;Cooke-Ariel, 1998;Furukawa et al, 1998;Khoury et al, 1992;Scheer et al, 2010;Thrall et al, 2007;White, 2003). By searching the database for these key words, evidence regarding behavioral risks factors triggering morning cardiac events was identified, and preventive patient education strategies to decrease morning onset of cardiac events are proposed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular disease is the most common cause of deaths among females and males in the developed countries (4); it is the cause of 12.8% of all the deaths (5), almost 83 million people have cardiovascular diseases in America (6). Cardiovascular diseases are also recognized as the most important causes of death in Iran; the study of death face in 18 cities of Iran showed that 46% of all the deaths were due to such diseases (3).…”
Section: Introductionmentioning
confidence: 99%